RETRACTED: Assessment of the effectiveness of state support of small and medium-sized enterprises - Korobov Sergey; Epinina Veronica; Usacheva Irina; Moseyko Victor (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001